A case of chronic paraffin pneumonitis. Issue 6 (November 1970) - Salm, R.; Hughes, E. W.
Abstract : A case of chronic paraffin pneumonitis is reported which had remained undiagnosed during life. The patient, a woman aged 48 at death, was subsequently found to have been taking regularly very large doses of liquid paraffin during a decade or more. The main clinical, radiological and histological features are discussed.